Games in the net - Del Puerto Paule Ruiz, María (2002)
A web site of quiz games has been developed, which incorporates some advances in comparison with most of the known web sites of the same kind. Registered users can play in two different types of single games, in one of them the system allows the player to select the topic of the question. There is also a group game option which deals with several topics. The way in which the system treats each player depends on his level, which is dinamically assigned to him according to his scores. There are also many other posibilities such as record management, rankings, single games management (saving, continuing and deleting games) implemented in the system. It must be emphasized the warnings and expulsions philosofy which punishes those players booked in a group game who do not play propperly .